2019
DOI: 10.1109/twc.2019.2902557
|View full text |Cite
|
Sign up to set email alerts
|

Backscatter Data Collection With Unmanned Ground Vehicle: Mobility Management and Power Allocation

Abstract: Collecting data from massive Internet of Things (IoT) devices is a challenging task, since communication circuits are power-demanding while energy supply at IoT devices is limited. To overcome this challenge, backscatter communication emerges as a promising solution as it eliminates radio frequency components in IoT devices. Unfortunately, the transmission range of backscatter communication is short. To facilitate backscatter communication, this work proposes to integrate unmanned ground vehicle (UGV) with bac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…It is obvious that, the performance for two schemes increases by increasing SNR value, the performance of the proposed scheme achieved with perfect CSI is the best, and imperfect CSI can cause performance degradation in system achievable rate. Meanwhile for the same SNR, as 2 a decreases, the gap between the achievable rate achieved with perfect CSI and imperfect CSI becomes smaller. For instance, at SNR = 12dB, the gap corresponding to 2 a = 0.1 is 2.59, and corresponding to 2 a = 0.05 is 2.21.…”
Section: Numerical Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…It is obvious that, the performance for two schemes increases by increasing SNR value, the performance of the proposed scheme achieved with perfect CSI is the best, and imperfect CSI can cause performance degradation in system achievable rate. Meanwhile for the same SNR, as 2 a decreases, the gap between the achievable rate achieved with perfect CSI and imperfect CSI becomes smaller. For instance, at SNR = 12dB, the gap corresponding to 2 a = 0.1 is 2.59, and corresponding to 2 a = 0.05 is 2.21.…”
Section: Numerical Resultsmentioning
confidence: 94%
“…Figure 2 shows the influence of SNR on the achievable rate for three schemes under variances of CE errors 2 a = 0.05 and 2 a = 0.1, a ∈ {i, rr}. It can be seen that the achievable rate of all schemes increases as SNR increases from 0 to 24, and for the same 2 a , our proposed SVD-based GP scheme always achieves the best performance compared to the Unaided scheme and SVDbased AO scheme in this range of SNR. Furthermore, it can be observed that with the same SNR, decreasing the 2 a causes an increase in the value of achievable rate for all the schemes.…”
Section: Numerical Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…With the positions of anchor points, the next step is to determine the visiting sequence of these points via route planning. The route planning problem is a constrained discrete optimization problem [4], [5], where the constraints guarantee: 1) the robot returns to the starting point; 2) the robot visits the selected vertices; 3) the planned path is connected. Conventionally, tree search algorithms, e.g., branch-and-bound (B&B), can be adopted for systematically pruning out ineffective solutions, leading to significant reduction of the computational complexity compared to exhaustive search while guaranteeing optimality.…”
Section: Route Planningmentioning
confidence: 99%
“…Furthermore, the communication performance of UAV-enabled communications can be improved by exploiting UAVs' high mobility via appropriate trajectory design [2]- [5]. Although such performance improvement can also be achieved in the unmanned ground vehicle (UGV) communications [9], [10], designing UAVs' trajectories has much fewer constraints than designing UGVs' routes, such as obstructions and road restrictions, thus UAV-enabled communications have more degree of freedom in performance optimization.…”
Section: Introductionmentioning
confidence: 99%